Geometrizando no segundo ciclo :relato de uma intervenção pedagógica voltada à construção de conceitos geométricos no ensino fundamental - Azevedo, Ivanilka Lima de (2005)
This work has proposed to relate the experience product of a pedagogical intervention, performed in a public institution of teaching situated in this capital. It had as objective to validade the applying of a teaching module of geometry, more specifically about the conceptions of perimeter and área in the second cycle of fundamental teaching. This dissertation has presented the problematic which involves the teaching of geometry in different contexts. It has adopted the broach of the radical constructivism while methodological theoretical referencial through which it has tried to explain the phenomena that involves the teaching and the apprenticeship. It appropriates Jean s Piaget contributions related to the development stages, while referencial that will dialogue in the search by sense and comprehension of the geometric apprenticeship process and it runs over Richard s Skemp (1980) theory in order to explicit the student s apprenticeship according to the levels of instrumental comprehesion and relacional comprehension . The research has presented datum related to initial diagnosis evaluantion, the pedagogical intervention and analysis of the activities and students perfomance displaying still the results of the final evaluation. According to the results got, we could check the students group growth front to the acquisition of the concepts of perimeter and área in comparison with the previous knowledges presented in the initial diagnosis evoluation of the students participants of the research. We have concluded evaluating the objectives of the research, connecting the strategies and reasoning employed by the students in order to resolve the questions and then to reach the objectives proposed by the teaching module. We have presented still the main obstacles to the apprenticeship of such concepts